Legal Protection of Muslim Tourists in Islamic Religious Tourism in Malaysia: Reality and Challenges - Farahiyah Izni W Abd Rahman, Wan; Ahamat, Haniff (International Journal of Engineering and Technology, 2018)
Islamic Religious Tourism (Hajj and Umrah) services have emerged in recent years. Malaysia has become one of the key players in this fast growing segment. It is caused by better condition of the economy in Malaysia so that raising awareness of the Malaysian people to do the Sunnah (practice) that they believed. Despite this remarkable development, there have been many consumer complaints related to Umrah services in Malaysia. In fact, consumer claims against the travel agents related to Umrah package were the top in the list of services cases filed in the Tribunal for Consumer Claims (TCC) for the past many years. This article seeks to analyse the current application of the Hajj and Umrah services in Malaysia. It then attemps to identify problems related to it. The article then seeks to suggest proper ways on how to overcome the said challenge and problem. Being qualitative in nature, this study collects relevant framework which include laws, regulations and guidelines which are related to Umrah travel agencies services. The purpose is to analyse the adequacy of the existing consumer protection laws in protecting Muslim tourists. The study discovers the lacunae in the existing legal protection for Muslim tourists which renders the protection to be inadequate. The reserachers find that inadequacy of existing consumer legislation has led to the existing problem. Therefore, clear and definite legal instrument are needed to protect the rights of Muslim tourists as consumers in Islamic Religious Tourism.Â Â